The Validity of STEM Learning Tools Development through Project Based Learning (PjBL) to Improve Students’ Spatial Ability - Rizki Julina; Rahmah Johar; M. Syukri (Proceedings of AICS - Social Sciences, 2018)
The 2013 curriculum is developed with refinements of mind-set, one of them is a reinforcement of multidisciplinary learning, or commonly known as STEM (Science, Technology, Engineering, and Mathematics). Learning tool as one of learning support facilities also should be developed following the development of the 2013 curriculum. However, STEM learning tools are still unavailable. STEM implementation can be successful if supported by programs that are based on best practices for program design. One of the learning models that support them is PjBL (Project Based Learning). Also, there is an ability that is closely related to STEM implementation, namely spatial ability. Therefore, the purpose of this research was to develop STEM learning tools through PjBL to improve students’ spatial ability which valid. Learning tools developed were lesson plans, project worksheets, student worksheets, AutoCAD 2D Guideline, and spatial ability tests. This research was development research. The instrument used was validation sheets. The validation phase STEM-PjBL learning tools consisting of lesson plans, project worksheets, student worksheets, and spatial ability tests consisted of two phases. It was because only three of five validators who stated that the learning tools had been possible to use with minor revisions in the first phase. These results indicated that the learning tools were not however valid. As a result, the learning tools needed to be revised following the comments and suggestions provided by the validators. After that, the learning tools were validated again by the validators. The second phase validation result was all validators stated that the learning tools had been possible to use. In contrast to these tools, the AutoCAD 2D Guideline was only validated once because, in the first phase validation, all validators stated that the AutoCAD 2D Guideline was worth using with minor revision. Thus, STEM-PjBL learning tools to improve students' spatial ability have met the valid criteria.Keywords: development, learning tools, STEM, project-based learning, spatial ability.